The effectiveness of soundscape for a pleasant environment - Hj. Baharuddin, Zainul Mukrim; Ismail, Muhamad Amirulaizat (2016)
The concern on quality of soundscape has greater impact to urban environment around the globe. This paper presents a research on the effectiveness of soundscape in creating a pleasant environment which brings the idea of the soundscape, the collection of type and characteristic of sounds that emanate from natural landscapes and manmade features into a research and application focus. Thus, the aim of the paper is to provide attractive and effective soundscape to create a pleasant environment in urban area. This research argues what are the factors that influence pleasant soundscape environment. There are two urban parks around Kuala Lumpur have been selected as place of observation. Data gathered under the under the literature review and the observation during soundwalks. The results have presented that both sites need to promote sound enhancements to provide a better environment for users as well as encourage them to make their activities and attract more users to utilize the area. Therefore, a good quality of soundscape would encourage public user to have their leisure activities as well as living in healthy conditions as well as having pleasant environment.